Changes in motor strategies across age performing a longswing on the high bar - Albert, B.; Michel, M.; Rosa, A.-B. (Research Quarterly for Exercise and Sport, 2013)
Purpose: Improvements in motor performance and coordination may be impacted by the interaction of practice and organismic constraints. It has been proposed that these aspects of motor learning are achieved at a different time rate: first, during placement of the events (performance), and second, segmental spatiotemporal relationships (coordination). We focused on the acquisition of the longswing in high bar as one basic skill in gymnastics. The aim of this study was to determine how longswing performance and coordination change to increase swing amplitude as age and expertise increase. Method: One hundred and thirteen male gymnasts were classified into 5 distinct age groups (G1, G2, G3, G4, and G5) on the basis of the national competition rules. Longswing performance (swing amplitude and event placements) and coordination (positive and negative areas in the continuous relative phase) were measured for each group. Results: Analyses of variance revealed that the adequate placement and coordination of the earlier events were achieved in younger groups (G1, G2), while later events and their coordination were accomplished by the older groups (G3 through G5). Conclusion: Our results suggested that the process of longswing acquisition, as age and expertise increase, follows a progression parallel to the temporal occurrence of the task events, instead of the proposed learning sequence of event placement first and then coordination.